Discrimination against women in CEDAE convention: A critical study in light of the Holy Quran post graduate students at Qatar University as a model / Fatemaelzahraa Elsied Aly Mohammed Ismail - Fatemaelzahraa Elsied Aly , Mohammed Ismail (2019)
This dissertation is an analytic study of discrimination against women in the Convention on the Elimination of all forms of Discrimination against women "CEDAW" in light of the Holy Quran. It introduces the definition of feminism, its origin, development, and the feminist ideological trends in Western, Arab and Islamic thought. It also presents the main and most important symbols in feminism and their roles in declarations, conferences and international conventions, highlighting CEDAW as the subject of the study. The study is concerned with criticizing and analyzing the concepts related to discrimination against women which were released in CEDAW regarding the social, family, economic and political rights of women. The most important rights are equality and discrimination between men and women, men’s maintenance and control over women (al-willayah), marriage to non-Muslim, guardianship (al-qawamah), owning property, inheritance, governing a state or working as a judge, and finally witnessing. Based on Quranic texts and rational evidences, these rights were objectively criticized through stating which of them were in accordance with it achieving its objectives without conflict or contradiction, and which of them were in contrary to it. The study in the fifth final chapter concluded with a field study which aimed at measuring the awareness and identifying the views on the provisions stated in CEDAW and their compatibility with Islamic Law as well as their applicability in the contemporary Islamic reality. In order to achieve these aims, a questionnaire was distributed to post-graduate students, MA and PhD, at Qatar University for the academic year 2017-2018. The study adopted the historical, descriptive, analytical, critical and social approach. The study reached several conclusions the most important of which is that CEDAW does not correspond to the Islamic perception on some issues of discrimination against women. That is because Islam in setting up rights and duties does not emanate from the principle of equality between men and women, but rather it emanates from the principle of justice and integrity among the members of societies.